PENGARUH BUDAYA ORGANISASI, DISIPLIN KERJA, SERTA SEMANGAT KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS PADA DINAS PENDIDIKAN DAN KEBUDAYAAN KABUPATEN PADANG LAWAS) - Pemilu Rasmi Harahap (Jurnal Ilmiah Cano Ekonomos, 2021)
The purpose of the study is to determine the simultaneous and partial influence between organizational culture, work discipline and work morale on employee performance.The research method used is a quantitative method, And the data analysis technique used isdescriptive analysis and multiple linear regression analysis. The results of the study ofmultiple linear regression obtained regression equation Y = 14.308 + 0.281X1 + 0.082X2 -0.012 X3, the coefficient of determination obtained an R value of 0.469, the results of theresearch from the T test of organizational culture variables showed Tcount> Ttable ie3.359> 1.8698, so it can be concluded that (X1) has a significant effect on employeeperformance variables (Y). Work discipline variable shows Tcount <Ttable that is 0,700<1,8698, so it can be concluded that (X2) does not significantly influence employeeperformance (Y). The morale variable shows that Tcount <Ttable is Thitung -0, 087<1.98698, so it can be concluded that (X3) does not significantly influence employeeperformance (Y). F test results show Fcount> Ftable is 8.336> 2.71.